The Effect of Different Extraction Procedures on Antioxidant Activity of Garlic (Allium sativum L.) Essential Oil - Van Khanh, Nguyen; Thi Nhai, Do; Thanh Tung, Bui; Thanh Hai, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 36 No 3DO - 10.25073/2588-1132/vnumps.4213, 2020)
This paper studies the effect of different extraction procedures such as soxhlet extraction using n-hexane, distillation method and supercritical extraction (SFE) on the physicochemical properties of garlic essential oil. The yield of garlic essential oil by soxhlet extraction, steam distillation and SFE-CO 2 methods was approximately 0.441, 0.124 and 0.465 %, respectively. The results of the oil analysis by gas chromatography/mass spectrometry method show the presence of five major compounds, including diallyl sulfide, diallyl disulfide, 3-vinyl-1,2-dithiacyclohex-4-ene, 3-vinyl-1,2-dithiacyclohex-5-ene and diallyl trisulfide. The antioxidant activity of the essential oil obtained by the SFE-CO 2 method was significantly higher than by the distillation method, but was lower than the acid ascorbic one. Keywords Garlic essential oil, SFE, GC-MS, antioxidant activity, extraction. References [1] R. Lawrencea, K. Lawrenceb, Antioxidant activity of garlic essential oil (Allium Sativum) grown in north Indian plains, Asian Pacific Journal of Tropical Biomedicine 1 (2011) 51-54. https://doi.org/10.1016/S2221-1691(11)60122-6. [2] Dziri, H. Casabianca, B. Hanchi, K. Hosni, Composition of garlic essential oil (Allium sativum L.) as influenced by drying method, Journal of Essential Oil Research 26 (2014) 91-96. https://doi.org/10.1080/10412905.2013.868329.R. [3] Li, W. Chen, W. Wang, W. Tian, X.Z. Rrui, Extraction of essential oils from garlic (Allium sativum) using ligarine as solvent and its immunity activity in gastric cancer rat, Medicinal Chemistry Research 19 (2010) 1092-1105. https://doi.org/10.1007/s00044-009-9255-z. [4] M.K. Gafar, A.U. Itodo, A. A. Warra, L. Abdullahi, Extraction and Physicochemical Determination of Garlic (Allium sativum L) Oil, International Journal of Food and Nutrition science 1 (2012) 4-7. [5] A.P. Sa´nchez-Camargo, J.A. Mendiola, E. Iba´n˜ez, M. Herrero, Supercritical Fluid Extraction, Reference Module in Chemistry, Molecular Sciences and Chemical Engineering (2014) 1-17. https://doi.org/10.1016/b978-0-12-409547-2.10753-x. [6] A. Rafe, M. S. Nadjafi, Physicochemical characteristics of garlic (Allium sativum L.) oil: Effect of extraction procedure, International Journal of Nutrition and Food Sciences 3 (2014) 1-5. https://doi.org/10.11648/j.ijnfs.s.2014030601.11. [7] J. M. del Valle, C. Mena, M. Budinich, Extraction of garlic with supercritical CO2 and conventional organic solvents, Brazilian Journal of Chemical Engineering, 25 (2008) 535-542. https://doi.org/10.1590/S0104-66322008000300011. [8] A.E. Andreatta, G. Foco, G. Mabe, S.B. Bottini, Extraction of garlic oil with quasi-critical solvents, 4th Mercosur Congress on Process Systems Engineering (2014) 1-9. [9] H. Kamali, N. Aminimoghadamfarouj, E. Golmakani, A. Nematollahi, The optimization of essential oils supercritical CO2 extraction from Lavandula hybrida through static-dynamic steps procedure and semi-continuous technique using response surface method, Pharmacognosy Res 7 (2015) 57-65. https://doi.org/10.4103/0974-8490.147209. [10] L.D. Lawson, Z.J. Wang, B.G. Hughes, Identification and HPLC quantitation of the sulfides and dialk(en)yl thiosulfinates in commercial garlic products, Planta Med, 57 (1991) 363-370. https://doi.org/10.1055/s-2006-960119. [11] E. A. O'Gara, D. J. Hill, D. J. Maslin, Activities of Garlic Oil, Garlic Powder, and Their Diallyl Constituents against Helicobacter pylori, Applied and Environmental Microbiology 66 (2000) 2269-2273. https://doi.org/10.1128/aem.66.5.2269-2273.2000. [12] X. Qiao, Molecular distillation separation and purification of essential oils of garlic, Food science Shandong 5 (2007) 60. [13] M. Iranshahi, A review of volatile sulfur-containing compounds from terrestrial plants: biosynthesis, distribution and analytical methods, The Journal of Essential Oil Research, 24 (2012) 393-434. https://doi.org/10.1080/10412905.2012.692918. [14] M. Corzo-Martı´nez, N. Corzo, M. Villamiel, Biological properties of onions and garlic, Trends in Food Science & Technology 18 (2007) 609-625. https://doi.org/10.1016/j.tifs.2007.07.011. [15] K. Khoshtinat, M. Barzegar, M. A. Sahari, Z. Hamidi, Comparison of Antioxidant and Antibacterial Activities of Free and Encapsulated Garlic Oil with Beta-cyclodextrin, Applied food biotechnology 3 (2016) 254-268. https://doi.org/10.22037/afb.v3i4.12631.